Immunohistochemical expression of heat shock proteins, p63 and androgen receptor in benign prostatic hyperplasia and prostatic carcinoma in the dog. (25th July 2014) - Romanucci, M.; Frattone, L.; Ciccarelli, A.; Bongiovanni, L.; Malatesta, D.; Benazzi, C.; Brachelente, C.; Della Salda, L.
Abstract: This study compared heat shock proteins Hsp60, Hsp72 and Hsp73, along with p63 and androgen receptor (AR) immunoexpression between 16 cases of benign prostatic hyperplasia (BPH) and 11 prostatic carcinomas (PCa) in dogs. The proportion of Hsp60‐positive cells was higher in PCa compared with BPH ( P = 0.033), whereas the frequency and intensity of Hsp73 immunostaining did not differ significantly between the two groups. Hsp72‐immunostained nuclei formed a discontinuous layer along the basement membrane in BPH, whereas cells in this layer in PCa were negative or weakly positive. Hsp72 nuclear score showed significant positive associations with both p63 ( P = 0.016) and AR ( P = 0.009) scores. Double immunofluorescence revealed Hsp72‐p63 and Hsp72‐AR co‐expressions in basal cell nuclei. Aberrant cytoplasmic p63 immunolabelling was observed in 3 of 11 PCa cases. These results suggest a role of the combined expression of Hsp72, p63 and AR in basal epithelial cells in canine BPH and PCa.